REPRESENTASI TOXIC RELATIONSHIP DI SERIES EUPHORIA - Bashori, Rila Rahmaniyah; Tsuroyya (The Commercium, 2025)
Adolescence is a period of change from childhood to adulthood. As they get older, an adolescent expands their network of friends to interact. This interaction is to fulfill their social needs, one of which is a romantic relationship. This research aims to focus on discussing toxic relationships in the series Euphoria (2019) because there are still many people who do not realize that they are in a toxic relationship. They even think that the toxic treatment they have received is a form of attention and affection from their partner. Charles Sanders Peirce semiotics was chosen because it is able to provide in-depth meaning about toxic relationships in films and series through the triadic model of sign, object, and interpretant. The results of this study show that victims of toxic relationships are not only women who experience them but men can also experience them. Characterized by possessiveness, invasion of privacy, regulator, deflector, full dependence, manipulation, to verbal and physical violence to experience depression due to dependence.